ANALISIS SISTEM INFORMASI MANAJEMEN PEMBIAYAAN PADA PT. FEDERAL INTERNATIONAL FINANCE CABANG PEMATANG SIANTAR - ROSMANI SINAGA (LP2MTBM MAKARIOZ, 2019)
This research was conducted at PT. Federal International Finance Branch Range. Information system is a system that is structured in a business venture or increases the company's operational activities and helps management in making decisions, to fulfill the implementation of policies in the company. This study aims to determine the stages of financing at PT. Federal International Finance Branch Range and to find out the Management System for Giving PT. Federal International Finance Branch Range. Formulation of the problem in this study is how the stages of financing at PT. Federal International Finance Branch Range and how the Management System Provides financing PT. Federal International Finance Branch Range. The research method used in this research is descriptive method. Descriptive method is an analysis used to analyze data by describing or describing data that has been collected as it is without the intention of making conclusions that apply to the general or generalizations. The results of this study are the analysis of the financing management system and the provision of financing at PT. Federal International Finance Branch The range has been effective where the company has made a policy in giving financing to consumers with the separation of duties in a clear and firm organizational structure between the parts involved so that it can help finance activities assisted by a good internal supervision system of PT. The Federal International Finance Branch of Pematang Siantar should further reinforce the application of prudence that has been established in the system and procedure of granting and must be more selective in determining the credit financing facilities in accordance with the ceiling.